CFD Study on the Influence of Liquid Viscosity on the Swirling Gas-Liquid Flow - Ryan Anugrah Putra; Habib Luthfi Ash Shiddiqie; Indro Pranoto (LPPM Politeknik Aceh Selatan, 2022)
Swirling two-phase flow is important in industrial mixing and separation systems. In this work, the effect of liquid viscosity was investigated numerically using the Euler-Euler Computational Fluid Dynamics (CFD) model where the liquid and the gas acted as the continuous and dispersed phases, respectively. CFD simulations were performed to model the gas-liquid flow inside a horizontal pipe equipped with a static mixer element with liquid viscosities of 1, 5, 10, and 50 cP. The gas volume fraction contours in the central axial plane show that the evolution of gas distribution is strongly influenced by the liquid viscosity, especially in the region downstream of the element. The calculated results show that the higher the viscosity, the shorter the gas core downstream of the element. Gas separation after the element occurs over a shorter distance with higher liquid viscosity. A possible explanation is that the swirling flow decays faster at higher liquid viscosities, and the buoyancy force dominates over the centrifugal force.